‘Tu m’embrasses encore, et c’est mon pied dans les pompons !’ Comment construit-on le sens ? - Gilles Corminboeuf (Discours)
This study concerns French constructions producing a hypothetical interpretation composed of two juxtaposed or and-connected assertions such as You say one more word (and) I’m leaving. The introductory assertion expresses a fact that is at odds with elements of the situation of utterance. Indeed, it is quite obvious that the addressee is not talking in the situation of utterance: You say one more word can’t be a statement, and if it were it would be of poor informative content. I suggest an analysis of these constructions on the interface between syntax and pragmatics. These binary constructions present a mismatch between a formal structure (an assertion) and some pragmatic requirements usually linked to it (commitment, for example). These assertions – expressed under a “validation key” – increment the common ground with two items of information: (i) the validity of a state of affairs O; (ii) the allocation of a modal commentary to this fact, for example . I try to understand how this modal commentary is inferred. In my view, this inference is produced by two information sources in competition: a linguistic one – the state of affairs O is asserted – and an extralinguistic one – the experimental truth refutes the validity of O.